Development of a Rapid Method for the Determination of Caffeine in Coffee Grains by GC-FID-A Fully Validated Approach - Ioannis N. Pasias; I. Kiriakou; Charalampos Proestos (MDPI AG, 2017)
A simple method for the determination of caffeine in coffee grains by GC-FID (Gas Chromatography-Flame Ionisation Detector) is presented in the current work. The method was fully validated according to ISO (International Organization for Standardization) 17025 requirements and European Commission regulations. The accuracy, as provided by recovery experiments, was higher than 93%, and the precision, as provided by the (%) relative standard deviation under reproducibility conditions, was lower than 5%. A vast number of independent parameters that lead in the increase of uncertainty of methods were investigated. The analysis was performed without use of an internal standard, which was proven to be reliable according to several validation methods. The method was applied in real samples, and possible health claims were investigated.